Glass balls/binder bulk lift and start of mixing - Gill, Philip (Cranfield University, 2018)
TYPE-II.avi: High speed video of glass balls/binder bulk lift and start of mixing on Resonant Acoustic Mixer.
Keywords: 'Resonant acoustic mixing'; 'EOE'; 'Chemical Engineering not elsewhere classified'; 'Manufacturing Engineering not elsewhere classified'; 'Process Control and Simulation'